REAKSI INVESTOR TERHADAP SUSPENSI SAHAM TRAM - Penta Widyartat; Mukhlas Adi Putra; Muhammad Fauzi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
TRAM shares are shares with the largest number of shares in the mining sector. TRAM's shares are shares of PT Trada Alam Minera Tbk, which is currently suspended from the IDX. The suspension by the IDX followed the appointment of Heru Hidayat, the main commissioner of PT Trada Alam Minera Tbk as a suspect in the Jiwasraya insurance corruption case. This research is a qualitative research that will examine the effect of TRAM stock suspension on the sale value of ADRO shares. ADRO shares are shares of PT Adaro EnergyTbk. ADRO shares are the second largest shares in the mining sector after TRAM shares. This research is a qualitative research using the independent t test which tests whether there is a difference in the trading value of ADRO shares before and after suspension of TRAM shares. From the research results obtained a significance value of 0.04, which means that there is a significant difference in the trading value of ADRO shares before and after the date of suspension of TRAM shares